Effect of Cytokinin (BA and KN) On Shoot Induction From Sugarcane Callus - Rahman, MM; Alam, R; Tarique, HM; Hussen, MAM; Azam, MG (Bangladesh Journal of Agricultural Research, 2022)
Abstract not available Bangladesh J. Agril. Res. 45(2): 209-213, June 2020